2006
DOI: 10.1016/j.jpainsymman.2006.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Low Morphine Doses in Opioid-Naive Cancer Patients with Pain

Abstract: Cancer pain can be managed in most patients through the use of the analgesic ladder proposed by the World Health Organization. Recent studies have proposed to skip the second "rung" of the ladder by using a so-called "strong" opioid for moderate pain. However, usual doses of strong opioids commonly prescribed for the third rung of the analgesic ladder may pose several problems in terms of tolerability in opioid-naive patients. The aim of this multicenter study was to evaluate the efficacy and tolerability of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 21 publications
1
51
1
Order By: Relevance
“…The results also indicated that morphine is well tolerated. These findings are supported by reports from other studies elsewhere which showed that only a small proportion of patients under morphine therapy stop the drug due to poor response or other reasons (Bercovitch et al, 1999;Mercadante et al, 2006). In this study the caregivers had positive attitude towards the use of morphine and that they followed analgesic ladder recommended by WHO when prescribing and administering morphine to patients (WHO, 1990).…”
Section: Discussionsupporting
confidence: 85%
“…The results also indicated that morphine is well tolerated. These findings are supported by reports from other studies elsewhere which showed that only a small proportion of patients under morphine therapy stop the drug due to poor response or other reasons (Bercovitch et al, 1999;Mercadante et al, 2006). In this study the caregivers had positive attitude towards the use of morphine and that they followed analgesic ladder recommended by WHO when prescribing and administering morphine to patients (WHO, 1990).…”
Section: Discussionsupporting
confidence: 85%
“…This rate was considered acceptable, given the reported need to switch to other opioids from morphine because of unfavorable responses in the cancer population 20 . The percentage of patients who discontinued TP (7%) seems to be even less than patients treated with oral morphine (13%), transdermal buprenorphine (15%), and transdermal fentanyl (about 14%) reported in previous studies with a similar design and duration [14][15][16] . In studies of non-cancer pain, TP was associated with a lower rate of discontinuation in comparison with oxycodone 7,8,10 .…”
Section: Discussionmentioning
confidence: 69%
“…7 (14) 5 (10) 3 (6) 4 (10) 4 (10) NSAIDs -paracetamol n (%) 7 (14) 2 (4) 3 (6) 2 (5) 4 (10) opioid-naive patients with oral morphine 14 , transdermal buprenorphine 15 , and transdermal fentanyl 16 . The reduced tendency to increase the dose, already observed in animal models 5,6 , may reflect a less toleragen effect of TP, possibly due to its pharmacological characteristics with a dual analgesic mechanism 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The other was where patients either considered their level of pain could be managed without the use of rescue morphine; or introduced to opioids for the first time through this mode of delivery resulted in physical and cognitive effects regarded as intolerable. For opioid naive patients 31 particularly, their experiences of adverse effects resulted in limited use or ended use, at least at this stage in their pain. For those who were opioid tolerant but limited their intake of rescue morphine, we posit that this was as a result of the permissiveness of rescue morphine and that there was a lack of equilibrium in the trade-off between their perceived need for relief and side effects 11 .…”
Section: Discussionmentioning
confidence: 99%